Respuesta :

Answer:

See below

Step-by-step explanation:

x=a-2by^2   Subtract 'a' from both sides

x -a = - 2 by^2     divide both sides by - 2b

(a-x)/2b = y^2    sqrt both sides

y =  +- sqrt ( (a-x)/2b))

Hi1315

Answer:

y = ± [tex]\sqrt{\frac{(a-x)}{2b}}[/tex]

Step-by-step explanation:

x = a - 2by²

Take -2by² to the left side.

x + 2by² = a

Take x to the left side.

2by² = a - x

Divide both sides by 2b.

y² = [tex]\frac{(a-x)}{2b}[/tex]

Now remove the y square.

y = ± [tex]\sqrt{\frac{(a-x)}{2b}}[/tex]